2018
DOI: 10.1038/s41419-018-0512-2
|View full text |Cite
|
Sign up to set email alerts
|

HBx-induced S100A9 in NF-κB dependent manner promotes growth and metastasis of hepatocellular carcinoma cells

Abstract: Hepatocellular carcinoma (HCC) is associated with hepatitis B virus (HBV) infection. Myeloid-specific S100 proteins (S100s), namely, S100A8, S100A9 and S100A12, have been recently recognized as newly discovered damage-associated molecular patterns (DAMPs) that are correlated with progression in pathogen of infectious diseases. However, whether S100s are regulated by HBV and involved in HBV-related hepatocarcinogenesis are still unclear. Here, we found that all expression levels of myeloid-specific S100s (S100A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
56
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 57 publications
(56 citation statements)
references
References 48 publications
0
56
0
Order By: Relevance
“…The specificity of Ihh and HN antibodies used in this study has previously been validated and well characterized by using with negative control normal IgG isotype (3335). Rabbit anri‐proliferating cell nuclear antigen (PCNA) pAb (36) (ab‐18197; Abcam, Cambridge, United Kingdom) was used to assess proliferation in mouse growth plates. The sections were incubated at 4°C overnight.…”
Section: Methodsmentioning
confidence: 99%
“…The specificity of Ihh and HN antibodies used in this study has previously been validated and well characterized by using with negative control normal IgG isotype (3335). Rabbit anri‐proliferating cell nuclear antigen (PCNA) pAb (36) (ab‐18197; Abcam, Cambridge, United Kingdom) was used to assess proliferation in mouse growth plates. The sections were incubated at 4°C overnight.…”
Section: Methodsmentioning
confidence: 99%
“…14,17 Briefly, immunostaining analysis was independently performed by two clinical pathologists. The embedded-tissues were cut into 5-μm thick sections placed on adhesion microscope slides (Citoglas, China) and stained with H-E (Novland, China).…”
Section: Histopathology and Immunohistochemistrymentioning
confidence: 99%
“…H-E and IHC were done as previously described. 14,17 Briefly, immunostaining analysis was independently performed by two clinical pathologists. Five fields were randomly selected per sample.…”
Section: Histopathology and Immunohistochemistrymentioning
confidence: 99%
“…As a homodimer, A9 potently activates inflammation via Toll-like receptor 4 (TLR4). [18][19][20][21][22][23][24][25][26][27][28][29][30] As a heterocomplex with S100A8 (A8/A9, also known as calprotectin), it is antimicrobial (Figure 1a). [31][32][33][34][35][36][37][38][39][40][41][42][43][44] A9 exacerbates endotoxin-induced shock in mice.…”
Section: Introductionmentioning
confidence: 99%
“…A9 acts as a Damage-Associated Molecular Pattern (DAMP), activating NF-Band other cytokines through Tolllike receptor 4 (TLR4). [18][19][20][21][22][23][24][25][26][27][28][29][30] The interaction interface(s), affinity, and stoichiometry for the A9/TLR4 interaction are not known. A small region of A9 has been suggested to form part of the A9/TLR4 binding surface, 55 but no mutant of A9 has been identified that substantially compromises its activation of TLR4.…”
Section: Introductionmentioning
confidence: 99%